Economically important cephalopods of southern Angola, with a focus on the artisanal jig fishery - Vázquez Morán, Chénelle Lesley (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science)
The global decline in marine finfish stocks has been met with a concomitant expansion of fisheries for cephalopods. Despite the increase in the exploitation and commercialization of cephalopods, there is a dearth of scientific information for over 90% of the extant species and this is even more marked in the developing world. Angolan capture fisheries production noted a tenfold increase in cephalopod landings between 1994 and 2003. One of the important fisheries is a cephalopod directed jig fishery that targets the squid Loligo reynaudii and the cuttlefish Sepia vermiculata in southern Angola, however, there is a complete lack of socio-ecological information available for this fishery. Hence the aim of this thesis was to provide basic biological and demographic information on L. reynaudii and S. vermiculata distributed off the coast of southern Angola, assess the importance and dependence of local artisanal fishers on these two species and examine the current management strategies and policies in the region This study found that the artisanal cephalopod jig fishery is critical for the livelihoods of the coastal communities of southern Angola, particularly due to the limited alternative income generating opportunities available. The cephalopod jig fishery is highly labour intensive, with fishers spending a considerable amount of time per day, drifting over known fishing grounds. Catch composition of the artisanal jig fishery indicated that squid is the dominant species within the fishery, in terms of numerical abundance and weight. The productivity and progression of the fishery is hampered by a number of ecological, socio-economic and governance constraints, as highlighted by socio-economic surveys conducted with local squid fishers. Such constraints include, but are not limited to declining catches, increased negative interactions with seals, increased inter-sector competition, lack of infrastructure, poor quality fishing equipment as well as a lack of communication and support from government officials. To examine aspects of the biology and demography of L. reynaudii, whole specimens were collected monthly, from the two primary fishing areas in southern Angola; Namibe and Tombua, during two main sampling periods, June 2008 "“ May 2009 (Period 1) and June 2014 "“ May 2015 (Period 2). Male L. reynaudii were found to be significantly larger in size and weight than females, however both the average and maximum dorsal mantle length (DML) decreased between sampling periods. Length-at-50% maturity was larger for male L. reynaudii (170.47 mm DML "“ 1st period, 165.44 mm DML "“ 2nd period) than female L. reynaudii (114.71 mm DML "“ 1st period, 109.43 mm DML "“ 2nd period). Gonadosomatic indices (GSI) varied significantly during month and season for both sexes. Peak GSI coincided with a low catches in the artisanal jig fishery suggesting that the population may undergo a spawning migration away from fishing grounds, during late spring and summer. The theory of a seasonal spawning migration is further supported in this study by the low abundance of juvenile and sub-adult L, reynaudii collected during the study, along with the inability to detect egg beds in known fishing grounds. Stomach content analysis indicated that teleosts were the most important dietary item (66.3% F of the stomach contents). Trachurus capensis and Engraulis encrasicolus are both highly abundant small pelagic fishes in the cold nutrient rich waters of the Benguela Current and dominated the diet of sampled squid during autumn and winter months. It is likely that the prevalence of large, adult squid off the coast of Angola, as observed within the current study, may be ascribed to the suitable environmental conditions and the abundance of suitable prey. The results from the current study indicate that the southern Angolan subpopulation reveals similarities to that of the West Coast subpopulation of squid in South Africa, with regards to demographics and reproductive characteristics. It is likely that the population in southern Angola is an extension of the South African subpopulation of L. reynaudii on the western extremities. To examine the basic population biology and ecology of S. vermiculata off southern Angola whole specimens were collected from the fishery between December 2014 and April 2015. Morphological results indicate clear sexual dimorphism in soft part characteristics, cuttlebone and beak morphometry. Length-at-50% maturity was smaller in male S. vermiculata (217.53 mm DML) than female S. vermiculata (231.13 mm DML), although these differences were not significant. Stomach content analysis indicated that S. vermiculata predominantly fed on teleost species which were found within 64.5% of stomachs. Teleosts were more dominant in the diet of male S. vermiculata (78.6% F) than female S. vermiculata (53.0% F), which ate a more varied diet including crustaceans (41.2% F) and cephalopods (17.7% F). Availability and abundance of cuttlefish in Namibe indicates that the species may undergo a spatio-temporal shift in distribution, with majority of the artisanal catches of S. vermiculata occurring during summer months. The results from the current study highlights the fisheries potential of L. reynaudii and S. vermiculata and the dependence of artisanal fishers in southern Angola on cephalopods, and more specifically squid. The development of sustainable fisheries management strategies for the artisanal cephalopod jig fishery is critical, particularly as the global exploitation of cephalopods continues to increase with declining finfish populations. Failure to implement management strategies may remove this critical economic safety net for vulnerable coastal communities which have little alternative livelihood opportunities. Ongoing ecological research, a co-management approach and an increased consideration of local ecological knowledge will assist in designing appropriate management plans for the southern Angolan cephalopod jig fishery.
Keywords: Loligo reynaudii; Sepia vermiculata; Loligo fisheries -- Angola; Small-scale fisheries -- Angola; Marine ecology